Syndromal mental retardation due to mutations in a regulator of gene expression. - Gibbons, R; Picketts, D; Higgs, D (1995)
Mental handicap is a common clinical problem that has been a relatively neglected area of research. Though the causes are varied and complex, molecular biologists are making progress in understanding the mechanisms in some cases, particularly where there are distinguishing phenotypic or genetic markers. The fortuitous association of alpha thalassaemia with a form of mental retardation has allowed us to define a specific X-linked syndrome (ATR-X). Positional cloning was used to define a disease interval and examination of candidate genes demonstrated that mutations in a gene, XH2, showing homology to the SNF2 superfamily were responsible for this syndrome. The complex ATR-X phenotype suggests that this gene, when mutated, down-regulates the expression of several genes including the alpha-globin genes indicating that it could be a global transcriptional regulator. It is conceivable that this mechanism is involved in other forms of syndromal mental retardation.